Infanticide and expulsion of females in a cooperative mammal. - Clutton-Brock, T H (1998)
In cooperative groups of suricates (Suricata suricatta), helpers of both sexes assist breeding adults in defending and feeding pups, and survival rises in larger groups. Despite this, dominant breeding females expel subordinate females from the group in the latter half of their (own) pregnancy apparently because adult females sometimes kill their pups. Some of the females that have been expelled are allowed to rejoin the group soon after the dominant female's pups are born and subsequently assist in rearing the pups. Female helpers initially resist expulsion and repeatedly attempt to return to their natal group, indicating that it is unlikely that dominant females need to grant them reproductive concessions to retain them in the group.